Ekofeministična teologija soodvisnosti - Furlan-Štante, Nadja (Poligrafi, 2021)
This article addresses the issue of social and environmental (in)justice thro-ugh the lens of Christian ecofeminism and its ethic of interconnectedness and ecological responsibility for all of creation. Because ecofeminism connects the exploitation of women with the exploitation of creation (nature), I use the central research methodology of Christian ecofeminist hermeneutics to formulate a central research question: first, an analysis of Christian ecofeminism’s positi-on on social and ecological (in)justice, then an analysis of the positive implica-tions for Christian theology and for the pursuit of social and ecological justice.although climate change disproportionately impacts female populations, in par-ticular the reproductive health of poorer women, women are often excluded from environmental decision-making processes. Women around the world are already more affected by polluted air, limited access to clean water, and increased exposure to toxic chemicals, and climate change exacerbates these threats. Sensitivity to the impacts of climate change also provides women with a unique experiential kno-wledge that they can use to make an important contribution to efforts to increase climate resilience and sustainability, as well as to improve awareness and attitudes toward environmental issues and nature in the world’s religions. For ecofeminists, the environmental crisis is a reality, a threat, and a warning to modern humani-ty. Climate change, global warming, loss of biodiversity and other processes that are supposedly the result of pollution and long-term overuse and exploitation of natural resources are certainly a reflection and consequence of man’s global con-sumer-imperialist attitude towards nature.
Keywords: Christianity; climate change; ecofeminism; ekofeminizem; Ekologija; environmental (in)justice; Feministična teologija; Feminizem; Krščanstvo; okoljska nepravičnost; Okoljska pravičnost; Podnebne spremembe; ranljivost; vulnerability; women; ženske; Ženske in krščanstvo